Novel point mutation in fibrinogen (Innsbruck; BβArg44Gly) - Würtinger, P.; Griesmacher, A.; Ivaskevicius, V.; Biswas, A.; Zehetbauer, S.; Oldenburg, J.; Hohenstein, K.; Weigel, G. (Hämostaseologie, 2015)
This is a report of a novel fibrinogen point mutation (fibrinogen Innsbruck), a C/G point mutation at position 220 of exon two of the fibrinogen B|-chain leading to B|3Arg44Gly. The heterozygous mutation was found in a 16-year-old adolescent, hospitalized for the management of juvenile depression, who suffered from multiple epistaxis episodes during his stay at the university hospital in Innsbruck, Austria. Fibrinogen (based on the Clauss method) and fibrinogen antigen levels were highly discrepant (86 vs. 223 mg/dl) with thrombin time and reptilase time being in the respective upper reference ranges. Densitometric analysis of electrophoretic band pattern showed a reduction of a-polymers, indicating an impaired fibrin polymerization. This is in agreement with structural analysis, which showed a disturbance of the flexibility and structure of the region surrounding the fibrinoeptide B cleavage site. Fibrinogen Nijmegen, a mutation at the same position, is causative for thrombosis, whereas fibrinogen Innsbruck appears to lead to a bleeding tendency, illustrating that even mutations at the same position can cause contrary symptoms.
Keywords: Fibrinogen; congenital dysfibrinogenemia; fibrinogen mutation